Expressão de genes candidatos à determinação sexual em Astyanax scabripinnis (Teleostei: characidae) em animais com e sem cromossomos B - Castro, Jonathan Pena (Universidade Federal de São Carlos, 2019)
Fish are animals present in a wide variety of habitats and are distributed all over the world. The diversity of forms, behaviors and niches associated with the evolutionary characteristics of these animals make them important to the studies associated sex determination and sexual differentiation. Among the freshwater fish of the Neotropical region, the tetras of the genus Astyanax are one of most representatives. The A. scabripinnis species complex has been well studied about the origin, distribution and frequency of B chromosomes, being considered a model organism for evolutionary studies. Several studies with population inferences about the occurrence and frequency of B chromosomes show a seasonal variation between the sexes associated with the presence of supernumerary elements in A. scabripinnis. The hypothesis is that B chromosomes could have a possible influence on the reproductive processes of this species. Thus, the present study aimed to infer if there are differences in the levels of gene expression between specimens carrying and not carrying B chromosomes concerning some candidate genes for sex determination. The results obtained showed an over expression of the dmrt1 gene in maturing male gonads of animals with B chromosomes. For amh and foxl2 genes occurred an atypical expression in females carrying B chromosomes, where their expression patterns were more similar to those of males and the reverse to those of females that do not carry Bs. The male gonads were more conservative in relation to the expression of the amh and foxl2 genes, regardless of the maturation stage and the occurrence of the B chromosomes. These results indicate that B chromosomes are changing the profiles of the sex related genes, suggesting a possible adaptive role in extending the reproductive cycle.
Expression of candidates genes for sex determination in Astyanax scabripinnis (Teleostei: characidae) in animals with and without B chromosomes
Keywords: Peixes; Cromossomos Supranumerários; Diferenciação Sexual; Genes; Dmrt1; Foxl2; Amh; Fishes; Supernumerary chromosomes; Sexual differentiation; dmrt1; foxl2; amh; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL